Genesis and profanation of the other world: The interpretation of dreams - Drivet, Leandro (2017)
This paper addresses Nietzsche's reflections on the phenomenon of dreams as a crucial precedent of Freud's Die Traumdeutung. The works of Nietzsche and Freud are scrutinized to establish and compare the most relevant aspects of their understanding of dreams. The philosophical impact of both accounts is assessed in terms of the transvaluation of religious and metaphysical values, which reveals three epistemological shifts: the replacement of Metaphysics by History/Genealogy (Nietzsche) and by Metapsychology (Freud), and the expansion of rationality beyond the limits of consciousness (Nietzsche and Freud). Both authors are shown to consider dreams as figurative expressions of a postponed desire – or, more specifically, as the imaginary fulfillment (compensation) and the evocation/awakening of desire. As captured by the phrase “Memento libidines”, dreams are portrayed in both accounts as the guardians of sleep and desire. Finally, and in contrast with Assoun, a new interpretation of Thus Spoke Zarathustra is proposed, as an interpretation of the prophet's dreams reveals the presence of individual desire within the Nietzschean understanding of the phenomenon.